1973
DOI: 10.1111/j.1600-0773.1973.tb01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Induced Histochemical and Histological Alterations in Gastrointestinal Mucosa of Guinea Pigs

Abstract: Manganese chloride (10 mg/kg) was administered orally to guinea pigs for a period of 30 days. The histochemical and histological alterations in gastric mucosa consisted of loss of rnucin and pepsinogen granules, adenosine triphosphatase and glucose‐6‐phosphatase activities and patchy necrosis of the epithelium. The intestinal villi also showed patchy necrosis, the activities of adenosine triphosphatase and glucose‐6‐phosphatase were diminished while there was an increase in the activity of acid phosphatase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Although most reports on manganese toxicity have described the neurologic effects, manganese-induced lesions in other organs have also been observed. Chandra & Imam (1973) found patchy necrosis in the gastric mucosa of guinea pigs given manganese chloride (10 mg/kg) orally for 30 days. Hysell et a/.…”
Section: Discussionmentioning
confidence: 92%
“…Although most reports on manganese toxicity have described the neurologic effects, manganese-induced lesions in other organs have also been observed. Chandra & Imam (1973) found patchy necrosis in the gastric mucosa of guinea pigs given manganese chloride (10 mg/kg) orally for 30 days. Hysell et a/.…”
Section: Discussionmentioning
confidence: 92%
“…Metals like Mn, aluminum, mercury, and lead are known to be neurotoxic when present in high amounts in the body (Farina et al 2013). Although Mn toxicity in the brain has been studied extensively, scant attention has been paid to its possible toxic influence on enteric neurons despite cases of GI disturbances having been reported following chronic Mn exposure (Chandra and Imam 1973;Huang and Lin 2004). The present study revealed-for the first time, to our knowledge-that subchronic exposure to low doses of Mn can result in intestinal inflammation and metabolic dysregulation as evaluated in vitro and in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…However, these cases mainly refer to dysfunctions in the central nervous system (CNS) because they only sporadically mention the presence of GI-related abnormalities. Although the reported incidences of GI-related Mn toxicity are few, gastritis was identified in a man with acute Mn toxicity ( Huang and Lin 2004 ), and peptic ulcers were identified in guinea pigs orally administered Mn for 30 d ( Chandra and Imam 1973 ). As we begin to get clarity on the gut-brain axis, several theories regarding the development and progression of neurodegenerative diseases have focused on whether these neurological disorders begin in the enteric nervous system (ENS) ( Pellegrini et al.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of manganese was reported to be mainly affected the central nervous system, mainly the hypothalamus (10) . Also, the toxicity of manganese was suggested to affect the gastric mucosa (11) , and affected the hemoglobin synthesis (12) , and affecting testicular development (13) . The aim of this study is to investigate the effect of exposure to MnCl2 sub-lethal dose during prenatal development of the mice testes using MDA antibody as an immunohistochemical marker.…”
Section: Immunohistochemical Malondialdehyde Antibodies Changes Of Thmentioning
confidence: 99%